Missed diagnoses in prenatal evaluation by ultrasound: a retrospective analysis of four cases from a tertiary center for fetal malformations - Respondek-Liberska, Maria (Prenatal Cardiology, 2016)
Four cases of missed prenatal diagnosis by an experienced ultrasonographer and a fetal cardiologist from a tertiary teaching hospital are presented: 3-mm peri-membrane ventricular septal defect; hypoplastic aortic arch requiring prostin infusion after delivery; esophageal atresia with tracheal fistula; and right-sided diaphragmatic hernia. Freezed frames and cine loops of the prenatal ultrasound scans indicated that the missed anomalies were not visible in midgestation, suggesting that in the future, repeat ultrasound scans should be performed before delivery to reduce the occurrence of such diagnostic errors.